THREE YEARS OF THE CONFLICT IN UKRAINE – STRATEGIC GOALS OF RUSSIAN FEDERATION, USA AND EU - Zarić, Ivan; Ћеферјановић , Бојан (Politeia, 2025)
Even though the conflict in Ukraine is officially led between two sides, the Russian Federation (RF) and Ukraine, more countries are indirectly involved in this conflict. The majority of members of NATO (with the USA as the leader) and EU (led by Germany) provide military support to Ukraine, and in so doing they have, in a specific way, practically become actors in this conflict. Military assistance to Ukraine has predominantly consisted of armaments and military equipment, as well as training of Ukrainian soldiers, conducted on the territory of NATO Member States, but also on Ukrainian territory with military instructors hired by the Alliance. For purpose of better understanding of causes and consequences of the conflict in Ukraine it is necessary to consider in more detail the strategic goals of the RF, USA and EU which are directly or indirectly involved in events in Ukraine. In this paper conclusions were drawn predominantly by using the comparative method, in order to draw the parallels between the strategic goals of the RF, USA and EU. The data were collected by qualitative content analysis of statements of the relevant officials and the documents, and the presentation was in most partlaid out in chronological order. The basic hypothesis is the claim that the war between Russia and Ukraine represents the climax of confrontation not only between those two countries, but also of interests of West and the RF. In disciplinary terms, this paper is based on two approaches within the study of international relations - foreign policy analysis and geopolitics.